The Influence of Primary Teachers’ Attitude towards Planning for Instruction in Nandi South District - Jeruto , Fancy (African Journal of Education,Science and Technology (AJEST), 2014)
The major concerns in the 21st century to all educators is shifting education from mere learning to effective and efficient management of learning by teachers. Competence in instructional planning requires professional skills which can only be acquired through training and perpetuated by practice. The purpose of this study was to investigate teacher’s attitudes towards planning for instruction in primary schools in Nandi South district. The objectives of the study were to determine the teacher’s attitudes towards planning for instruction and establish the relationship between teacher’s attitudes and planning for instruction. This study subscribes to what Bower and Hilgard have termed general theories of instructions embodied in what recent psychologists term instructional theories. A descriptive survey design approach was employed in this study. Stratified and purposive sampling procedures were used to obtain trained primary school teachers used in the study. Questionnaires, observation and interview schedules were developed, validated and administered in the field to obtain data used in the present study. The results indicated that teachers understand and reasonably discuss the instructional planning process. However, it was revealed that they could not use available instructional ideas and materials to make and implement decisions that involve application of novel conceptual and practical technological ideas